PRESIDENTIAL APPROVAL IN CHILE, 1990-2018: VARIANCE IN U-SHAPED CURVES - Cabezas, José Miguel; Navia, Patricio (Revista Latinoamericana de Opinión Pública, 2019)
Studies on presidential approval in consolidated and emerging democracies identify similar determinants of popular support and show a common U-shaped cyclical pattern, with higher levels of support during the honeymoon period and in the last year of the presidential term and lower support in the in-between years. Since democracy was restored in 1990, Chile has had six presidential terms. With some nuances, presidential approval has evolved following the same cyclical pattern of higher approval at the beginning and end of the administrations. Using 66 presidential approval polls from Centro de Estudios Públicos between 1990 and 2018 (N=82,984), we assess the effect of party identification and economic vote variables on presidential approval. We show that party identification matters in the approval of all presidents. We also show that economic vote variables affect presidential approval for all presidents, though the effect was stronger for Ricardo Lagos (2000-2006) on average.